Efficacy and safety of convalescent plasma therapy in patients with moderate-to-severe COVID-19: A non-randomized comparative study with historical control in a referral hospital in Indonesia - Johan Kurnianda; Mardiah S. Hardianti; Teguh Triyono; Jarir A. Thobari; Ika Trisnawati; Calcarina F.R. Wisudarti; Usi Sukorini; Fuad Anshori; Syahru A. Setiawan; Meita Ucche; Abrid Farahnaz; Yana Suryani (Elsevier, 2022)
Background: Studies to confirm the efficacy and safety of convalescent plasma (CP) as an adjunctive treatment for COVID-19 are still required especially for the countries where standard treatments are unevenly distributed. Methods: A non-randomized comparative study was done from June - September 2020 in Dr. Sardjito Hospital, Yogyakarta, Indonesia. Plasma with anti-SARS-CoV-2 specific IgG titer of >1:320 were used. Primary end points were clinical and laboratory parameters outcome including BGA, chest X-ray, CT value, CRP, procalcitonin, IL-6, D-Dimer and ALC examined on day 1, 2 and 7 post-transfusion. Results: The experimental arm of this study consisted of 15 patients who received CP: 3 (20%) with moderate COVID-19 and 12 (80%) with severe COVID-19. There were 15 historical controls in this study. Ten recipients survived and 5 deceased (survival rate was 66.7%). There were higher rate of pneumonia resolution (OR 1.54, CI95% 0.33-7.23), ARDS resolution (OR 1.20, CI95% 0.25-5.84) and shorter median length of stay (20 vs 22 days, p = 0.41) among recipients compared to controls. Lower mortality rate was observed in recipients vs controls (33.3% vs 46.7% (OR 0.75, CI95% 0.17-3.33)). Median death onset was longer in recipient vs control (7th vs 1st day, p = 0.13). Survival analysis showed protective effect of CP (HR 0.69, CI 95% 0.21-2.27, p = 0.545). Higher CT value improvement (p = 0.51) and negative conversion rate (OR1.20, CI95% 0.25-5.84) were observed in recipients compared to controls. Sub-analysis showed more number of comorbidities, higher procalcitonin and higher D-Dimer among CP recipients who did not survive (p = 0.02 and p = 0.02 respectively). Lower CRP and procalcitonin, and higher ALC were found in survivors compared to non-survivors (p = 0.0437; p = 0.0049; and p = 0.0002 respectively). Conclusion: This study showed promising results for CP marked by improvements in clinical outcome, as well as significant reduction of inflammatory markers among recipients.